The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph19137639
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Peritraumatic Distress and Loneliness in Chinese Residents in North America: The Role of Contraction Worry

Abstract: The current study examined the association of COVID-19 contraction worry for self and for family members with COVID-19 peritraumatic distress and loneliness in Chinese residents in North America. A sample of 943 Chinese residents (immigrants, citizens, visitors, and international students) in North America completed a cross-sectional online survey during the second wave of the COVID-19 pandemic (between January and February 2021). Univariate analysis of variance (ANOVA) models identified possible sociodemograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
2
5
0
Order By: Relevance
“…Consistently, Statistics Canada found that reports of racially based attacks and forms of harassment against Chinese Canadians increased by 30% from the onset of the pandemic to May 2020 [19,20]. Our past work also identified discrimination (perceived or experienced) as a robust and strong risk factor for COVID-19-related risk perceptions [21] as well as mental health outcomes among Chinese Canadians during the pandemic [10,[22][23][24]. Increased incidences of racial discrimination, reports of higher anxiety symptoms among immigrant populations, and the cultural barriers/stigma around accessing mental health support make it essential to understand the risk factors for this population [10].…”
Section: Chinese Canadian Populationsupporting
confidence: 64%
See 1 more Smart Citation
“…Consistently, Statistics Canada found that reports of racially based attacks and forms of harassment against Chinese Canadians increased by 30% from the onset of the pandemic to May 2020 [19,20]. Our past work also identified discrimination (perceived or experienced) as a robust and strong risk factor for COVID-19-related risk perceptions [21] as well as mental health outcomes among Chinese Canadians during the pandemic [10,[22][23][24]. Increased incidences of racial discrimination, reports of higher anxiety symptoms among immigrant populations, and the cultural barriers/stigma around accessing mental health support make it essential to understand the risk factors for this population [10].…”
Section: Chinese Canadian Populationsupporting
confidence: 64%
“…Overall, these findings demonstrate how perceptual models may be a necessary approach for evaluating and identifying predictors of the pandemic's psychological impact. Among Chinese residents in Canada, COVID-19-related perceptions such as a self-contraction worry have been associated with higher distress and loneliness during the pandemic [22].…”
Section: Pandemic-related Variablesmentioning
confidence: 99%
“…There is also a possibility that individuals who are perceiving discrimination, or who have a personal connection to COVID-related cases, are experiencing higher levels of distress. In particular, worry about personally contracting COVID-19 has been significantly associated with COVID-19 peritraumatic distress [ 33 ]. Similarly, previous research showed that perceived and experienced racial discrimination serve as robust predictors for mental health condition among Chinese living in Canada [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Potentially those who felt confused might have attended to multiple (reliable or unreliable) sources of COVID-19 information, and may have been receiving conflicting information. This may increase their distress and uncertainty, and thus make them likely to perceive the pandemic as more threating [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the contagious yet invisible nature of COVID-19, a psychosocial toll is placed on individuals regardless of whether they have contracted the illness (Ahorsu et al, 2020). During the initial pandemic response, reports of elevated distress related to COVID-19 were evident (Best et al, 2021;Varga et al, 2021;Lee et al, 2022). Extant literature on fear of COVID-19 has yielded contrasting findings, with some suggesting greater fear of COVID-19 in younger adults (Bäuerle et al, 2020;Quadros et al, 2021) and others reporting no age differences (Luo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%